2021
DOI: 10.1038/s41467-021-21625-2
|View full text |Cite|
|
Sign up to set email alerts
|

A model for the fragmentation kinetics of crumpled thin sheets

Abstract: As a confined thin sheet crumples, it spontaneously segments into flat facets delimited by a network of ridges. Despite the apparent disorder of this process, statistical properties of crumpled sheets exhibit striking reproducibility. Experiments have shown that the total crease length accrues logarithmically when repeatedly compacting and unfolding a sheet of paper. Here, we offer insight to this unexpected result by exploring the correspondence between crumpling and fragmentation processes. We identify a phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Through repeated, uniaxial crumpling of Mylar sheets in a cylindrical setup, the authors found that the accumulated crease length evolves logarithmically in the number of crumpling cycles. In a subsequent study, a physical explanation for this robust logarithmic scaling was proposed by relating crumpling to a fragmentation process that dictates the subdivision of a sheet's surface into smaller facets over time [27]. The statistics of facet area in each crease pattern were consistent with an area-conserving fragmentation rate equation used previously to describe fracture phenomena [28].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Through repeated, uniaxial crumpling of Mylar sheets in a cylindrical setup, the authors found that the accumulated crease length evolves logarithmically in the number of crumpling cycles. In a subsequent study, a physical explanation for this robust logarithmic scaling was proposed by relating crumpling to a fragmentation process that dictates the subdivision of a sheet's surface into smaller facets over time [27]. The statistics of facet area in each crease pattern were consistent with an area-conserving fragmentation rate equation used previously to describe fracture phenomena [28].…”
Section: Introductionsupporting
confidence: 61%
“…The radially confined sheet has an effective thickness of 0.125 mm, while the remaining examples are 0.25 mm. Experimental studies of repeated cylindrical confinement have revealed remarkably robust properties in the accumulation of total crease length and the distribution of facet sizes, as previously described [26,27]. A possible application of numerical simulation would be to verify whether these statistical properties are universal to different modes of crumpling such as radial confinement, which may otherwise pose experimental challenges.…”
Section: Representative Examplesmentioning
confidence: 68%
“…23 The dynamics of crumpling 2D sheets (both athermal and thermal) in different contexts has also received attention in recent years. 77,78 In order to study the conformational behavior of sheets as a function of S and (k B T/k), we consider two geometric quantities: minimumvolume bounding ellipsoids and orientational covariance matrices. Minimum-volume bounding ellipsoids of sheets were calculated for snapshots of sheet configurations every _ gDt snap = 0.25 units of time via the following (dual) convex optimization problem: 79…”
Section: Conformational Behaviormentioning
confidence: 99%
“…The discovery of an alternative mechanism for surface scarring in a similar (though not mechanically identical) way to how paper creases when repeatedly crumpled [6] could also have practical applications-for example, in soft-robotics devices that fold [7] or in surface engineering for fluid transport [8]. Indeed, one could envision manipulating the surface tension of soft solids to "program" their creasing pattern with a view to controlling the transport of liquids over such surfaces.…”
Section: Vie W Poin Tmentioning
confidence: 99%